(untitled) (ENTHYMEMA, 2016)
Narrative Medicine is a clinical practice, a scholarly field, and a site of intensive research worldwide. This essay describes the inauguration of the field of narrative medicine in 2000 at Columbia University in New York, NY, USA and the principles and practices that have devolved from the initiating work. Clinical implications of narrative concepts of health care as learned from actual medical practice are described. The three movements of narrative medicine—attention, representation, and affiliation—are explored as means of engaging participants in creative acts of discovery and relation. Examples are provided of narratively-informed teaching and health care practice. Conceptual frameworks from aesthetic theory, phenomenology, literary and narrative theories, and cognitive sciences are advanced to portray the integrated study of individuals-in-the-world made possible by contemporary narrative medicine thought. Emerging concepts of enchantment, embodiment, and enactivism suggest future directions for the field.